Biofortified Yellow-Fleshed Potatoes Provide More Absorbable Zinc than a Commonly Consumed Variety: A Randomized Trial Using Stable Isotopes in Women in the Peruvian Highlands - Liria Domínguez, M.R.; Penny, M.E.; Kroon, P.A.; Burgos, G.; Dainty, J.; Zeder, C.; Zimmermann, M.; King, J.C.; Mithen, R.; Boy, Erick; Al-Jaiballi, O.; Fairweather-Tait, S. (Elsevier, 2023)
Abstract Background Zinc biofortified potatoes have considerable potential to reduce zinc deficiency due to their low levels of phytate, an inhibitor of zinc absorption, and their high consumption, especially in the Andean region Peru.